Inorganic crystal material and preparation method and application thereof
Through the lifting method of Dy4Al2O9 laser matrix crystal, the 580nm yellow light laser output is achieved using 448nm pump, which solves the problems of complexity and low efficiency of the yellow light laser device in the prior art, and obtains high power and high efficiency yellow light laser.
Patent Information
- Application Number
- CN202211153149.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-21
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-09-21
AI Technical Summary
The existing yellow light laser implementation method relies on nonlinear means, the device is complex, the cost is high and the conversion efficiency is low, making it difficult to obtain yellow light band lasers with high beam quality and high performance.
Dy4Al2O9 is used as the laser matrix crystal, and grown by lifting method, and super strong fluorescence with a peak wavelength of 580nm is generated in the visible light band using a 448nm pump, directly realizing the yellow laser output.
The high-power yellow light laser output is achieved, which avoids the loss of the nonlinear conversion process, has self-activation performance and high phonon energy, and enhances the fluorescence emission and laser emission efficiency.
Smart Images

Figure CN115852486B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to an inorganic crystal material, belonging to the field of crystal materials. Background Art
[0002] Yellow lasers can be used in many fields such as sodium beacon lasers, biomedicine, laser display, etc., and have attracted great attention due to their unique advantages. At present, most yellow lasers are realized through nonlinear means, and the device system is very complex, costly, and has low conversion efficiency. 3+ The gain medium can directly obtain yellow light laser. The device is simple and compact, and the loss caused by the nonlinear conversion process can be avoided.
[0003] The development of LD-pumped all-solid-state lasers is driven by application needs and technological development. Before the 1990s, lasers mainly relied on lamp pumps, and then the successful development and development of LDs with power of tens of watts greatly promoted the development of all-solid-state lasers and laser crystals. 3+ The absorption peak in the blue light band matches the wavelength of GaN-based LD, thus driving the Dy 3+ Research on yellow laser crystals. Aluminates as the matrix material of laser crystals have the advantages of good physical and chemical properties, high hardness, excellent thermal properties, and insolubility in acid and alkali. Typical representatives include Y3Al5O 12 , YAlO3, CaGdAlO4, CaYAlO4 crystals, etc. These aluminates generally have higher melting points and melt with the same composition, and are suitable for growth by the Czochralski method. 3+ Weak absorption is very unfavorable for achieving yellow laser output. Therefore, in-depth research and development of new laser crystal materials for direct pumping by LD pump sources to achieve yellow laser output is an ideal solution for obtaining high beam quality and high performance yellow band lasers. Summary of the invention
[0004] According to the first aspect of the present application, a new crystal material Dy4Al2O9 is provided, and the crystal is grown by the Czochralski method. The crystal is an excellent laser matrix crystal, which uses 448nm pumping to produce super strong fluorescence with a peak wavelength of 580nm in the visible light band, and the crystal can be used to generate yellow laser of ~580nm.
[0005] An inorganic crystal material, the chemical formula of the inorganic crystal material is Dy4Al2O9; it belongs to the monoclinic system and the P21 / c space group;
[0006] The unit cell parameters of the inorganic crystal material are: α=71.24~71.25°, β=90°, γ=90°, Z=4.
[0007] Optionally, the unit cell parameters are α=71.240~71.245°, Density: 6.7-6.8 g·cm -3 .
[0008] Specifically, the chemical formula of the crystal material is Dy4Al2O9, which belongs to the monoclinic system, the P21 / c space group, and the unit cell parameters are α=71.244°, β=90°, γ=90°, Z = 4, density is 6.73 g cm -3 .
[0009] Optionally, the crystal structure of the inorganic crystal material is:
[0010] There are 60 atoms in a unit cell, consisting of nine different O sites, four Dy sites and two Al sites. The Dy ion has one 6-coordination and three 7-coordination situations, while the two O ions are both 6-coordinated. Thus, the Dy-O connection forms a decahedron and an octahedron. Al1 and Al2 are both adjacent tetrahedral coordinated, and two adjacent Al-O tetrahedrons share one O ion, forming a curved Al-O-Al bridge.
[0011] Specifically, there are four inequivalent Dy 3+ Location: In the first Dy 3+ Position, Dy in the first Dy 3+ Location, Dy 3+ With six O 2- The atoms combine to form a DyO6 octahedron, which shares vertices with five AlO4 tetrahedra and edges with two equivalent DyO7 hexagonal pyramids;
[0012] The distribution range of Dy-O bond distance is
[0013] In the second Dy 3+ Location, Dy 3+ With seven O's 2- The atoms combine to form a distorted DyO7 hexagonal pyramid, which shares vertices with three AlO4 tetrahedra, edges with two equivalent DyO6 octahedra, and edges with two AlO4 tetrahedra;
[0014] The distribution range of Dy-O bond distance is
[0015] In the third Dy 3+Location, Dy 3+ Combined with seven O2 atoms;
[0016] The distribution range of Dy-O bond distance is
[0017] In the fourth Dy 3+ Location, Dy 3+ Combined with seven O2 atoms;
[0018] The distribution range of Dy-O bond distance is
[0019] There are two inequivalent Al in the unit cell. 3+ Site: In the first Al 3+ In the middle, Al 3+ With four O 2- The atoms combine to form an AlO4 tetrahedron, which shares vertices with two equivalent DyO7 hexagonal pyramids, shares vertices with two equivalent DyO6 octahedra, shares vertices with an AlO4 tetrahedron, and shares edges with a DyO7 hexagonal pyramid;
[0020] The distribution range of Al-O bond distance is
[0021] In the second Al 3+ In the middle, Al 3+ With four O 2- The atoms combine to form an AlO4 tetrahedron, which shares vertices with a DyO7 hexagonal pyramid, shares vertices with three equivalent DyO6 octahedra, shares vertices with an AlO4 tetrahedron, and shares edges with a DyO7 hexagonal pyramid;
[0022] The distribution range of Al-O bond distance is
[0023] Optionally, the inorganic crystal material is in block form;
[0024] The inorganic crystal material has at least one dimension with a size of 20 to 90 mm.
[0025] Optionally, the inorganic crystalline material has at least one dimension with a size of 20 to 85 mm.
[0026] Optionally, the absorption spectrum of the inorganic crystal material contains an absorption peak with a peak wavelength of 448 nm in the 445-455 nm band.
[0027] Optionally, in the fluorescence spectrum of the inorganic crystal material under 448 nm pumping, the 575-605 nm band contains an emission peak with a peak wavelength of 580 nm.
[0028] The crystal material Dy4Al2O9 has good physical and chemical properties (non-hygroscopic, insoluble in acid and alkali), high melting point, high mechanical strength, high thermal conductivity, high laser damage threshold, and high phonon energy.
[0029] According to a second aspect of the present application, a method for preparing the above-mentioned inorganic crystalline material is provided.
[0030] The method for preparing the inorganic crystal material described above adopts a Czochralski method and comprises the following steps:
[0031] The raw materials containing Dy2O3 and Al2O3 are mixed, pressed and sintered, placed in a pulling furnace to heat and melt, and a twisted iridium wire is used as a seed crystal for introduction. After the crystal is formed on the seed crystal, the crystal growth is carried out;
[0032] The growth conditions are:
[0033] The cooling rate is 1-10°C / h, the pulling rate is 0.5-1mm / h, the rotation rate of the seed crystal rod is 12-15rpm, and after the growth is completed, the crystal is lifted from the liquid surface and cooled to room temperature at a rate of 8-25°C / h;
[0034] The molar ratio of Dy2O3 and Al2O3 is Dy2O3:Al2O3=2:1.
[0035] Optionally, the melting temperature is 1917°C to 1947°C.
[0036] As an embodiment, the method for preparing the inorganic crystalline material comprises at least the following steps:
[0037] Dy2O3 and Al2O3 are used as raw materials, and the molar ratio of Dy2O3 to Al2O3 in the raw materials is Dy2O3:Al2O3=2:1. After the raw materials Dy2O3 and Al2O3 are mixed, a twisted iridium gold wire is used as a seed crystal for introduction to carry out crystal growth. The growth conditions are a cooling rate of 0.5-1 mm / h, a rotation rate of the seed crystal rod of 12-15 rpm, and after the growth is completed, the crystal is lifted from the liquid surface and cooled to room temperature at a rate of 8-25°C / h to obtain the bulk crystal material with at least one dimension greater than 20 mm. Among them, the purity of Dy2O3 is 99.99%, and the purity of Al2O3 is 99.99%.
[0038] According to a third aspect of the present application, there is provided an application of the inorganic crystal material described above or the inorganic crystal material prepared according to the preparation method described above.
[0039] The inorganic crystal material described above or the inorganic crystal material prepared according to the preparation method described above is used to realize the output of laser with a wavelength in the 580nm yellow light band under 448nm pumping.
[0040] According to a fourth aspect of the present application, a laser is provided.
[0041] A laser comprises the inorganic crystal material described above and / or the inorganic crystal material prepared according to the preparation method described above.
[0042] Optionally, the laser further comprises a fiber-coupled semiconductor end-face pumping module, a beam coupling system, an input mirror, and an output mirror;
[0043] The beam coupling system is located behind the fiber-coupled semiconductor end-face pumping module;
[0044] The input mirror is located after the beam coupling system;
[0045] The output mirror is located behind the input mirror;
[0046] The inorganic crystalline material is located between the input mirror and the output mirror.
[0047] Optionally, the pump source of the fiber-coupled semiconductor end-face pump module is a 448nm blue light LD, adopting an end-pump mode;
[0048] The coupling mirror of the beam coupling system is a plane mirror;
[0049] The input mirror is a concave mirror.
[0050] The beneficial effects of this application include:
[0051] 1) The inorganic crystal material provided in the present application has self-activation performance. The self-activated Dy4Al2O9 crystal can achieve high-power output of 580nm yellow light laser under 448nm pumping.
[0052] 2) The inorganic crystal material provided by the present application, the self-activated Dy4Al2O9 crystal and the ordinary Dy 3+ Compared with the doped aluminate crystal, Dy4Al2O9 has a higher phonon energy (Raman spectroscopy test of the crystal shows that the phonon energy is about 888 cm -1 ), which is beneficial to enhance the fluorescence emission of the crystal in the yellow light band, thereby increasing the laser emission power and efficiency; Dy4Al2O9 has a relatively large emission cross section in the yellow light band, which is beneficial for yellow light laser output; due to the self-activation of Dy ions, there is no need to dope other ions in the Dy4Al2O9 crystal, avoiding problems such as lattice mismatch and facilitating the growth of high-quality crystals. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 It is a crystal of Dy4Al2O9 grown by the Czochralski method.
[0054] Figure 2 This is a schematic diagram of the crystal structure of Dy4Al2O9.
[0055] Figure 3 It is a comparison between the X-ray powder diffraction pattern obtained by fitting the single crystal data and the two sets of data actually measured.
[0056] Figure 4 This is the room temperature absorption spectrum of Dy4Al2O9 crystal.
[0057] Figure 5 This is the fluorescence spectrum of Dy4Al2O9 crystal in the visible light band under 448nm pumping.
[0058] Figure 6 It is Dy4Al2O9 crystal in Dy 3+ : 4 F 9 / 2 Fluorescence decay curve of energy level.
[0059] Figure 7 This is a schematic diagram of a laser device that uses Dy4Al2O9 crystal. DETAILED DESCRIPTION
[0060] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0061] Unless otherwise specified, the raw materials and reagents used in this application were purchased from commercial sources and used directly without treatment. The instruments and equipment used adopted the schemes and parameters recommended by the manufacturers.
[0062] In the embodiment, the instrument used for the crystal pulling method growth is a self-made crystal growth furnace, the crucible used is an iridium crucible of Φ60mm×60mm, and the raw materials used are Dy2O3 and Al2O3 with a purity of 99.99%.
[0063] In the examples, the single crystal structure of the sample was analyzed by X-ray spectrum recording on a Mercury CCD single crystal diffractometer, the structure was solved using Olex2 (Dolomanov et al., 2009), and refined using the ShelXL (Sheldrick, 2015) program.
[0064] In the examples, powder X-ray analysis of the samples was carried out on a Miniflex 600 powder diffractometer.
[0065] In the examples, the absorption spectra of the samples were measured on a Lambda950 absorption spectrometer produced by Pekin-Elmer; and the fluorescence spectra under 448 nm pumping were measured on a FLS980 fluorescence spectrometer produced by Edinburgh, UK.
[0066] Example 1 Preparation of large-size single crystal samples of Dy4Al2O9
[0067] Dy2O3 and Al2O3 are prepared according to the following chemical reaction formula:
[0068] 2Dy2O3+Al2O3→Dy4Al2O9
[0069] Dy2O3 and Al2O3 were weighed according to the above molar ratio, wherein the amount of Dy2O3 was 1.6 mol, and the molar ratio of Dy2O3 to Al2O3 was 2:1. After being evenly mixed, they were put into an iridium crucible of Ф60mm×60mm, placed in a homemade crystal growth furnace, and slowly heated at a rate of 200℃ / h until the raw materials melted. The temperature was kept constant for half an hour to completely melt the raw materials (the temperature was 1937℃ at this time), and then the iridium wire with a twist at the bottom was used as a seed crystal for introduction. After the crystal was formed on the iridium wire, crystal growth was carried out. During the growth process, the cooling rate was set to 7.5℃ / h, the pulling speed was set to 0.9mm / h, and the rotation rate of the seed crystal rod was set to 13rpm. After the growth was completed, the crystal was lifted from the liquid surface and cooled to room temperature at a rate of 20℃ / h to obtain a yellow transparent crystal with a diameter of 22mm and a length of 85mm, as shown in FIG. Figure 1 shown.
[0070] Example 2 Crystal structure characterization of samples
[0071] A small piece was broken off from the surface of the grown bulk crystal, and a sample with good crystallinity and size of 0.6×0.4×0.1mm was selected. 3 The Dy4Al2O9 single crystal was subjected to X-ray single crystal diffraction analysis.
[0072] The results show that Dy4Al2O9 crystals belong to the monoclinic system, space group P21 / c, unit cell parameters α=71.244°, β=90°, γ=90°, Z = 4, density is 6.73 g cm -3 The structure of Dy4Al2O9 crystal is as follows Figure 2 As shown in the figure, there are 60 atoms in a unit cell, consisting of nine different O sites, four Dy sites and two Al sites. The Dy ion has one 6-coordinated and three 7-coordinated situations, while the two O ions are both 6-coordinated. Thus, the Dy-O connection forms a decahedron and an octahedron. Al1 and Al2 are both adjacent tetrahedral coordinated, and two adjacent Al-O tetrahedra share an O ion, forming a curved Al-O-Al bridge. There are four inequivalent Dy ions in the unit cell. 3+ Sites; four inequivalent Dy 3+ The sites are: in the first Dy3+ Position, Dy in the first Dy 3+ Location, Dy 3+ With six O 2- The atoms combine to form a DyO6 octahedron, which shares vertices with five AlO4 tetrahedra and edges with two equivalent DyO7 hexagonal pyramids; the distribution range of Dy-O bond distance is In the second Dy 3+ Location, Dy 3+ With seven O's 2- The atoms combine to form a distorted DyO7 hexagonal pyramid, which shares vertices with three AlO4 tetrahedra, edges with two equivalent DyO6 octahedra, and edges with two AlO4 tetrahedra; the distribution range of Dy-O bond distance is In the third Dy 3+ Location, Dy 3+ Combined with seven O2 atoms; the distribution range of Dy-O bond distance is In the fourth Dy 3+ Location, Dy 3+ Combined with seven O2 atoms; the distribution range of Dy-O bond distance is There are two inequivalent Al in the unit cell. 3+ Site: In the first Al 3+ In the middle, Al 3+ With four O 2- The atoms combine to form an AlO4 tetrahedron, which shares vertices with two equivalent DyO7 hexagonal pyramids, two equivalent DyO6 octahedra, one AlO4 tetrahedron, and one DyO7 hexagonal pyramid. The distribution range of Al-O bond distance is In the second Al 3+ In the middle, Al 3+ With four O 2- The atoms combine to form an AlO4 tetrahedron, which shares vertices with a DyO7 hexagonal pyramid, three equivalent DyO6 octahedra, an AlO4 tetrahedron, and an edge with a DyO7 hexagonal pyramid; the distribution range of Al-O bond distance is
[0073] The structure of the crystal sample was determined by powder X-ray diffraction. The theoretical XRD diffraction pattern obtained by crystal structure simulation was compared with the actual measured diffraction pattern. Figure 3 As shown in the figure, it can be seen that the positions of the diffraction peaks in the theoretical spectrum and the actual measured spectrum are consistent, indicating that the obtained sample is a high-purity crystal.
[0074] Example 3 Optical properties of samples
[0075] Take the sample and process it into a size of 5.0×5.0×1.0mm 3 Crystal sheet, both sides 5.0×5.0mm 2 Parallel polishing and spectral performance testing and research.
[0076] The results showed that the absorption spectra of the samples showed 12 Dy 3+ The characteristic absorption peaks of Dy are at 321, 353, 386, 448, 479, 752, 804, 897, 1073, 799, 1291 and 1697 nm, respectively. 3+ : 6 H 15 / 2 arrive 4 M 17 / 2 + 6 P 3 / 2 + 4 G 9 / 2 + 4 I 9 / 2 , 6 P 7 / 2 + 4 I 11 / 2 , 6 P 5 / 2 + 4 M 19 / 2 , 4 K 17 / 2 + 4 M 21 / 2 + 4 I 13 / 2 + 4 F 7 / 2 , 4 I 15 / 2 , 4 F 9 / 2 , 6 F 3 / 2 , 6 F 5 / 2 , 6 F 7 / 2 , 6 H 7 / 2 + 6 F 9 / 2 , 6 H 9 / 2 + 6 F 11 / 2 and 6 H 11 / 2 The absorption peak of 445-455nm is relatively wide, with a peak wavelength of 448nm. This absorption band matches the commercial InGaN semiconductor pump source, making the crystal very suitable for laser experiments using commercial 448nm diode pumping.
[0077] The room temperature fluorescence spectrum of the sample under 448nm pumping has a wide fluorescence emission band between 570 and 600nm, with a peak wavelength of 580nm, corresponding to Dy 3+ : 4 F 9 / 2 → 6 H 13 / 2 The half-maximum width (FWHM) is 12 nm, and the emission cross section calculated by the FL equation is 3.55×10 -21 cm 2 @580nm, the emission cross section is large, which is conducive to the realization of yellow laser output near 580nm.
[0078] According to the sample fluorescence decay curve, the Dy 3+ : 4 F 9 / 2 The fluorescence lifetime is 0.33 ms.
[0079] The absorption spectrum, fluorescence spectrum in the visible light band and fluorescence decay curve of the sample are shown as follows: Figure 4 , Figure 5 and Figure 6 shown.
[0080] The comprehensive research experimental results show that Dy4Al2O9 crystal is a very promising laser crystal material that can achieve 580nm band yellow light laser output.
[0081] Application of Example 4 in Laser Device
[0082] Take a good quality crystal sample and process it into a crystal rod with a size of 5mm×5mm×10mm. The two ends of the crystal are polished to 5mm×5mm and used in the laser device. The crystal is placed on a cooling device composed of a temperature control table and a copper block. During the experiment, the temperature of the crystal is maintained at 8°C, and the control accuracy is 0.1°C. In the experiment, a layer of indium paper is placed between the copper table and the crystal for better heat dissipation. The function of the filter is to filter out the 448nm pump light, and the function of the attenuation plate is to prevent the visible light spectrometer from saturation. Coaxial end-face pumping is adopted, and the pump light is focused on the center of the crystal after passing through a double-glued achromatic lens and a concave mirror 1. The laser resonant cavity consists of two concave mirrors. The transmittance of the concave mirror at 448nm is greater than 96%, the reflectivity at 580nm is greater than 99.7%, and the radius of curvature is -200mm. The schematic diagram of the experimental device is shown in the figure. Figure 7 The results show that the laser device using the Dy4Al2O9 crystal sample can achieve laser output in the 580nm band.
[0083] The self-activated Dy4Al2O9 crystal of the present invention is different from the ordinary Dy 3+Compared with doped aluminate crystals (reference: Ju Qiaojun, Shen Hua, Yao Wenming, et al. Semiconductor laser pumped Dy:YAG yellow laser [J]. Chinese Laser, 2017, 44(4): 0401004.), it has the following advantages:
[0084] The peak absorption wavelength of Dy4Al2O9 crystal in the blue light band is closer to the central wavelength of blue light LD. According to the literature, the central wavelength of Dy:YAG crystal is 447.3nm, while the absorption wavelength of Dy4Al2O9 crystal is at 448nm. Being close to the central wavelength of blue light LD is more conducive to the absorption of pump light by the crystal during laser experiments.
[0085] The emission half-width of Dy4Al2O9 crystal in the yellow light band is wider. According to the literature, the half-width of Dy:YAG crystal is less than 0.2nm, while the half-width of Dy4Al2O9 crystal is 12nm, which is 60 times that of Dy4Al2O9 crystal. The wider half-width is conducive to tuning the laser wavelength and improving the stability of the output laser.
[0086] Therefore, the self-activated Dy4Al2O9 crystal of the present invention is a very excellent yellow light laser gain material.
[0087] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. An application of an inorganic crystal material to realize the output of a laser with a wavelength in the yellow light band of 580nm under a 448nm pump, characterized in that: The chemical formula of the inorganic crystalline material is Dy4Al2O9; It belongs to the monoclinic system, P21 / c space group; The unit cell parameters of the inorganic crystal material are a=10.59~10.60Å, b=7.44~7.46Å, c=11.19~11.20Å, α=71.24~71.25°, β=90°, γ=90°, V=836.74~836.76Å 3 , Z=4; In the fluorescence spectrum of the inorganic crystal material under 448nm pumping, the 575-605nm band contains an emission peak with a peak wavelength of 580nm.
2. The use according to claim 1, characterized in that: The unit cell parameters are a=10.590~10.595Å, b=7.445~7.455Å, c=11.190~11.195Å, α=71.240~71.245°, V=836.745~836.755Å 3 , density is 6.7~6.8g·cm -3 .
3. The use according to claim 1, characterized in that: The inorganic crystal material is in block form; The inorganic crystal material has at least one dimension with a size of 20 to 90 mm.
4. The use according to claim 1, characterized in that: The absorption spectrum of the inorganic crystal material contains an absorption peak with a peak wavelength of 448 nm in the 445-455 nm band.
5. The use according to claim 1, characterized in that: The preparation method of the inorganic crystal material adopts a Czochralski method, comprising the following steps: The raw materials containing Dy2O3 and Al2O3 are mixed, pressed and sintered, placed in a pulling furnace to heat and melt, and a twisted iridium wire is used as a seed crystal for introduction. After the crystal is formed on the seed crystal, the crystal growth is carried out; The growth conditions are: The cooling rate is 1-10℃ / h, the pulling rate is 0.5-1mm / h, the rotation rate of the seed crystal rod is 12-15rpm, and after the growth is completed, the crystal is lifted from the liquid surface and cooled to room temperature at a rate of 8-25℃ / h; The molar ratio of Dy2O3 and Al2O3 is Dy2O3:Al2O3=2:
1.
6. The use according to claim 5, characterized in that: The melting temperature is 1917~1947℃.
7. The use according to claim 1, characterized in that: The application is a laser, and the laser comprises the inorganic crystal material; The laser also includes a fiber-coupled semiconductor end-face pump module, a beam coupling system, an input mirror, and an output mirror; The beam coupling system is located behind the fiber-coupled semiconductor end-face pumping module; The input mirror is located after the beam coupling system; The output mirror is located behind the input mirror; The inorganic crystalline material is located between the input mirror and the output mirror.
8. The use according to claim 7, characterized in that: The pump source of the fiber-coupled semiconductor end-face pump module is a 448nm blue light LD, which adopts the end-pump mode; The coupling mirror of the beam coupling system is a plane mirror; The input mirror is a concave mirror.
Citation Information
Patent Citations
Crystal material and preparation method thereof, and application of crystal material as laser crystal
CN111118603A